S1PR2 participates in intestinal injury in severe acute pancreatitis by regulating macrophage pyroptosis - Lin, Tianjiao; Peng, Mengyuan; Zhu, Qingyun; Pan, Xinting (Frontiers in Immunology, 2024)
Background: Severe acute pancreatitis (SAP) is an inflammatory disorder affecting the gastrointestinal system. Intestinal injury plays an important role in the treatment of severe acute pancreatitis. In this study, we mainly investigated the role of S1PR2 in regulating macrophage pyroptosis in the intestinal injury of severe acute pancreatitis.The SAP model was constructed using cerulein and lipopolysaccharide, and the expression of S1PR2 was inhibited by JTE-013 to detect the degree of pancreatitis and intestinal tissue damage in mice. Meanwhile, the level of pyroptosis-related protein was detected by western blot, the level of related mRNA was detected by PCR, and the level of serum inflammatory factors was detected by ELISA. In vitro experiments, LPS+ATP was used to construct the pyroptosis model of THP-1. After knockdown and overexpression of S1PR2, the pyroptosis proteins level was detected by western blot, the related mRNA level was detected by PCR, and the level of cell supernatant inflammatory factors were detected by ELISA. A rescue experiment was used to verify the sufficient necessity of the RhoA/ROCK pathway in S1PR2-induced pyroptosis.Meanwhile, THP-1 and FHC were co-cultured to verify that cytokines released by THP-1 after damage could regulate FHC damage.Our results demonstrated that JTE-013 effectively attenuated intestinal injury and inflammation in mice with SAP. Furthermore, we observed a significant reduction in the expression of pyroptosis-related proteins within the intestinal tissue of SAP mice upon treatment with JTE-013. We confirmed the involvement of S1PR2 in THP-1 cell pyroptosis in vitro. Specifically, activation of S1PR2 triggered pyroptosis in THP-1 cells through the RhoA/ROCK signaling pathway. Moreover, it was observed that inflammatory factors released during THP-1 cell pyroptosis exerted an impact on cohesin expression in FHC cells.The involvement of S1PR2 in SAP-induced intestinal mucosal injury may be attributed to its regulation of macrophage pyroptosis.